Novel Imaging Techniques in Rheumatic Diseases - Hemke, Robert; Mascarenhas, Vasco; Maas, Mario (Seminars in Musculoskeletal Radiology, 2018)
Since the introduction of new MR imaging techniques within the past two decades, the imaging assessment of joints in rheumatic diseases has changed considerably. MRI enables to evaluate both the inflamed synovial membrane as well as early structural damage. In the last few years, several new functional/metabolic MR imaging techniques have applied in rheumatic diseases, making it possible to evaluate the pathophysiology of the disease in greater detail. Moreover, they permit a more quantitative approach for the evaluation of disease activity and damage. Several functional imaging techniques in rheumatic diseases have been proposed for the evaluation and monitoring of disease status.
Keywords: magnetic resonance imaging; positron emission tomography; rheumatoid arthritis; juvenile idiopathic arthritis; spondylarthropathy